Serapan Hara N, P, K dan Hasil Biji Kedelai (Glycine max L. Merrill) pada Pemberian Bokashi Pelepah Pisang pada Tanah Pasir Pantai - Khavid Faozi; Prapto Yudono; Didik Indradewa; Azwar Ma'as (Vegetalika, 2019)
The ability of several soybean varieties to absorb nutrient nitrogen, phosphorus and potassium (NPK) may be different in the new growing environment in coastal sands which are treated with bokashi made from banana stem. The aim of this study was to determine the NPK nutrient uptake and the responses of several soybean varieties to the level of banana stem bokashi application in coastal sand fields and to determine the optimum dose based on the yield of soybean seeds. The research was a field experiment conducted for 4 months from January until April 2017. Pot experiments in the field have been done in Samas coastal sands, Srigading Village, Sanden Sub-district, Bantul Regency, Special Region of Yogyakarta. The factorial experiment (4x12) was repeated 3 times, arranged in a complete randomized block design (RCBD). The first factor was dose banana stem bokashi including 0, 20, 40, and 60 t.ha-1; was tested on 12 soybean cultivars namely Anjasmoro, Argomulyo, Burangrang, Demas 1, Dena 1, Devon 1, Gamasugen 1, Gema, Gepak Ijo, Grobogan, Kaba, and Slamet. The observational data were analyzed by the variant analysis of the error rate of 5% and if significantly different was followed by DMRT 5% error level. The results showed that bokashi made from the banana stem can be used as a soil enhancer for coastal sandy soil, as well as providing nutrients for the growth of soybean plants. Nutrient uptake of N, P, K, plant dry weight, and seed yields of Anjasmoro varieties, Argomulyo, Demas 1, Devon 1, Gepak Ijo, Kaba and Slamet increased with the application of banana stem bokashi at doses of  20 and 40 t.ha-1, and decreases at bokashi doses reaching 60 t.ha-1. The optimum dose of bokashi made from banana stem doses equals 35.80 t.ha-1 with a maximum seed yield of 22.24 g.pot-1.